FENOMENA HIJRAH DI INDONESIA: KONTEN PERSUASIF DALAM INSTAGRAM - Zahrina Sanni Musahadah; Sulis Triyono (Universitas Negeri Makassar, 2019)
Abstract: The Phenomenon of Hijrah in Indonesia: Persuasive Content of Instagram. This article purpose’s is to describe how the hijrah account declare the hijrah persuasive invitation. The Datas are lingual unit that from Instagram account and have hijrah invitation meaning, there are @berani hijrah, @pemudahijrah, anda #hijrah. The discourse analysis content use van Dijk Methode as the way with marking reading technique. Lingual units that are suspected of data are analyzed based on the semantic meaning of word selection and their social context through the agihmethode. The results of this study are (1) direct rethoric, (2) indirect rethoric, (3) use Hadis, prayer and hope, (4) use story, (5) expression, (6) majas and (7) repetition.